Dyke system planning: - Pham, Cong Huu (University of Bonn, 2009)
This book focuses on the social interaction of paddy farmers and landless people during the annual flood season from a local knowledge perspective. It will be argued that local knowledge turns into a strategic resource in the context of growing competition for decreasing natural water products